2022
DOI: 10.1186/s12864-022-08776-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and analysis of ACP gene family in Sorghum bicolor (L.) Moench

Abstract: Background Acyl carrier proteins (ACP) constitute a very conserved carrier protein family. Previous studies have found that ACP not only takes part in the fatty acid synthesis process of almost all organisms, but also participates in the regulation of plant growth, development, and metabolism, and makes plants adaptable to stresses. However, this gene family has not been systematically studied in sorghum. Results Nine ACP family members were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…They play a crucial role in the direct synthesis pathway of long-chain fatty acids and also have significant involvement in other cellular metabolic processes [30,31]. To date, numerous studies have focused on identifying and analyzing ACP family proteins in various plant species [16,[32][33][34], but there is a lack of research on the function and potential role of ACP gene families, specifically in Brassica. It is worth noting that the genomes of six Brassica species have already been sequenced and assembled [20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They play a crucial role in the direct synthesis pathway of long-chain fatty acids and also have significant involvement in other cellular metabolic processes [30,31]. To date, numerous studies have focused on identifying and analyzing ACP family proteins in various plant species [16,[32][33][34], but there is a lack of research on the function and potential role of ACP gene families, specifically in Brassica. It is worth noting that the genomes of six Brassica species have already been sequenced and assembled [20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of salt stress, the atacp5 mutant displays increased sensitivity compared to that of the wild type, while overexpression of AtACP5 enhances salt stress tolerance in transgenic Arabidopsis. Moreover, recent studies have identified certain SbACP (ACP in Sorghum bicolor) genes that contribute to drought and salt stress tolerance [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that ACP may be involved in various biological processes in response to environmental stress ( de Silva et al., 1990 ). For example, the expression of SbACP9 is up-regulated within 6-24 hours of water-deficient treatment in rice, showing a rapid and sustained response to drought stress ( Ge et al., 2022 ). In this study, ACP enzymes exhibited the promoting activity in all three heteromorphic leaves of P. euphoretic, indicating that ACP may play an important role in attenuating the effects of abiotic stress through leaf morphological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time polymerase chain reaction (qRT-PCR) was conducted in triplicate for each sample using ChamQ SYBR qPCR Master Mix (Low ROX Premixed) (Vazyme, Nanjing, China). The gene-specific primers for qRT-PCR listed in Supplementary Table S1 were used to amplify ZmACR genes by PCR under the following conditions: predenaturation at 95°C for 30 s, denaturation at 95°C for 10 s, annealing at 60°C for 30 s, and 40 cycles ( Ge et al., 2022 ). An ABI 7500 FAST Real-Time PCR System was used for qRT-PCR.…”
Section: Methodsmentioning
confidence: 99%